Towards a conceptual framework in understanding student dropout in Higher Education institutions - Ramrathan, Labby (South African Journal of Higher Education, 2016)
Higher education institutions within South Africa, in particular, have experienced high student dropout within undergraduate programmes. Reasons for such high dropout, as contained in the current literature suggests that the majority of students dropout because of student biographical and financial reasons. International literature suggests that student dropout are loacted within the discourse of students’ expereince of higher education. This paper reports on an institutional research on student dropout at a South African higher education institution with a view to explore, through a finegrained analysis the issues that one need to conceptualise when researching student dropout. Through the analysis of data generated through a mixed method approach, this paper presents a conceptual framework for exploring personal, biographical and institutional issues impacting on student dropout. Through this framework, new insights on this phenomenon are illuminated. The paper presents one such illumination relating to insideous institutional violence.